2013
DOI: 10.1155/2013/413092
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin a Enhances Transient Inactivating Potassium Current in Rat Hippocampal CA1 Neurons

Abstract: Saikosaponin a (SSa), a main constituent of the Chinese herb Bupleurum chinense DC., has been demonstrated to have antiepileptic activity. Recent studies have shown that SSa could inhibit NMDA receptor current and persistent sodium current. However, the effects of SSa on potassium (K+) currents remain unclear. In this study, we tested the effect of SSa on 4AP-induced epileptiform discharges and K+ currents in CA1 neurons of rat hippocampal slices. We found that SSa significantly inhibited epileptiform discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 2012 ) and inactivating K + current (Xie et al. 2013 ). It inhibits the activation of p38 MAPK, NF- κ B signaling pathways to attenuate neuropathic pain (Zhou et al.…”
Section: Ssamentioning
confidence: 99%
See 1 more Smart Citation
“… 2012 ) and inactivating K + current (Xie et al. 2013 ). It inhibits the activation of p38 MAPK, NF- κ B signaling pathways to attenuate neuropathic pain (Zhou et al.…”
Section: Ssamentioning
confidence: 99%
“… 2012 ; Xie et al. 2013 ; Yoon et al. 2012 , 2013 ), and chronic constriction injury rats (Zhou et al.…”
Section: Ssamentioning
confidence: 99%
“…SSa also exerts anti-epileptic activity by inhibiting the current of Nmethyl-D-aspartic acid (NMDA) and persistent sodium (Yu et al, 2012) and suppressing epileptiform discharges frequency and increasing the K + current (Xie et al, 2013). Furthermore, several studies showed that SSa alleviates the chronic constriction injury (CCI)-induced neuropathic pain and eliminates the traumatic brain injury-induced neurological function deficits (Mao et al, 2016) through inhibiting inflammatory factors and reducing P38 MAPK and NF-κB signaling pathway.…”
Section: Effects Of Sss On Central Nervous System (Cns)mentioning
confidence: 99%
“…One recent study in rat epilepsy models demonstrated that the inhibition of the N-methyl-D-aspartate (NMDA) receptor current and INaP may be the underlying mechanisms of saikosaponin's anticonvulsant properties [21]. Furthermore, the authors also demonstrated that saikosaponin enhances transient inactivating potassium currents in rat hippocampal CA1 neurons [22]. Chaihu longgu muli tang (TW-001) is based on chaihu and mixed with 12 other botanicals [23].…”
Section: Bupleurum Chinense (Chaihu)mentioning
confidence: 99%